Whatsapp Chatbot Autoresponder Berbasis Pencarian Artikel - Haddad Sammir; Khairil Hamdi; Budi Harto (Prosiding SISFOTEK, 2023)
Whatsapp is a popular messaging application with more than 2 billion active users worldwide. This application is not only used by individuals, but also by business and government users. Various WhatsApp-based services have emerged for various purposes, such as customer service, information services, and government services. WhatsApp is a de facto messaging application that is not only used by individuals, but also by business and government users. Various WhatsApp-based services have emerged for various purposes and are generally managed by humans. This research designs a WhatsApp chatbot application to automate responses to incoming questions using a search mechanism in the knowledge base and forwarding them to the questioner. The knowledge base in this research was implemented using a MySQL database. This knowledge base consists of two tables, namely the question table and the answer table. The question table stores commonly asked questions, while the answer table stores the answers to these questions. In this way, answering questions can be delegated to the application and reduce human workload. The WhatsApp chatbot application can be a solution to reduce the human workload in answering questions that come in via WhatsApp. This application can be implemented for various WhatsApp-based services, such as customer service, information services and government services